The influence of risk perception for COVID‐19 pandemic on posttraumatic stress disorder in healthcare workers: A survey from four designated hospitals. (16th February 2021) - Geng, Shiyu; Zhou, Yaoguang; Zhang, Wenyong; Lou, Anni; Cai, Yuhan; Xie, Jieying; Sun, Jing; Zhou, Wangmei; Liu, Weizhi; Li, Xu
Abstract: The aim of current study was to investigate risk perception of COVID‐19 pandemic, sleep quality and time change of leisure activity and their correlations with posttraumatic stress disorder (PTSD) in healthcare workers (HCWs) from four designated hospitals in China. Medical staffs ( n  = 317) from three designated hospitals in Guangdong Province and one designated hospital in Guangxi Province were surveyed on their demographic information, sleep quality and time change of leisure activity, risk perception of pandemic and PTSD symptoms (by using PTSD checklist for DSM‐5 (PCL‐5)). Hierarchical regression and structural equation model (SEM) were used to examine the correlated factors of PTSD. The prevalence of high level of PTSD symptoms (PCL‐5 > =33, a probable diagnosis of PTSD) was 10.7%. Regression analysis found that risk perception (dread: β  = 0.142, p  < 0.01; familiarity: β  = 0.203, p  < 0.01), sleep quality ( β  = 0.250, p  < 0.001), time change of leisure activity ( β  = −0.179, p  < 0.01), were independently correlated with PTSD severity, which was further confirmed by SEM. Locations of COVID‐19‐related hazards were significant different in cognitive map of risk perception between groups with high and low levels of PTSD symptoms. Risk perception of COVID‐19 pandemic influenced PTSD symptoms in HCWs. Adequate time for leisure activity and good sleep quality protected some HCWs against PTSD symptoms under the influence of pandemic. More researches were warranted to understand the path from pre‐factors of risk perception to its psychological consequences among HCWs.